The impact of digital influencers’ characteristics on purchase intention of fashion products - Gomes, M.; Marques, S.; Dias, Á. (Journal of Global Fashion Marketing, 2022)
Research on digital influencers’ role in marketing strategies under ongoing development. This study explores the role of digital influencer marketing on consumer purchase intention in fashion products. The goal is to investigate the direct and indirect relationships of trustworthiness, expertise, content quality, similarity, para-social interaction, and attitude towards sponsored posts on purchase intention. A mixed-method approach was conducted combining interviews with five digital influencers and a consumer-based survey with a sample of 206 fashion consumers, among them 96.1% were women and 51.5% were between 18 and 31 years old. Results indicate that blog content quality and para-social interaction positively influence purchase intention in fashion brands. Additionally, blog content quality plays a mediating role between trustworthiness and purchase intention. Moreover, consumers’ attitude towards sponsored posts influences directly and positively purchase intention and mediates the relationship between trustworthiness and purchase intention. Consumers’ attitude towards sponsored posts was also found to mediate the relationship between expertise and purchase intention. This study highlights the digital influencers’ marketing characteristics, which affect the fashion consumer purchase intention, enriching the research in this area and providing recommendations for further investigation. The results also highlight the importance of aligning communication strategies of fashion brands with influencers’ lifestyle.